Physical parameters and quality of mineral fertilizers in industries in Brazil (Research, Society and Development, 2022)
Currently, Brazil is the fourth country that most uses fertilizer, behind only countries such as the United States, India and China, and the main nutrient used by Brazil is phosphorus The use of fertilizers is essential for world agriculture. Since each ton of mineral fertilizer applied to one hectare, according to principles that allow maximum efficiency, is equivalent to the production of four new hectares without fertilization. Fertilizer is a mineral or organic substance, natural or synthetic, providing one or more plant nutrients. In 2020, 40,564,138 million tons of fertilizers were delivered to the national market, an increase of 12% compared to the previous year. Fertilizers can be found in three states, being solid (the most found in Brazil), liquid or gas. The quality characteristics of mineral fertilizers can be classified according to their nature into: physical, chemical and physical chemical characteristics. The physical characteristics of mineral fertilizers are: physical state, granulometry, hardness and density. Fertilizer efficiency is closely related to physical characteristics.